Preparation method of low-cost high-performance high-nickel positive electrode material

CN116404123BActive Publication Date: 2026-10-30CHINA ELECTRONIC TECH GRP CORP NO 18 RES INST
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211724110.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-30
Publication Date
2026-10-30
Estimated Expiration
2042-12-30

AI Technical Summary

Technical Problem

[0003]但是,由于高镍材料对水分敏感,传统烧结窑炉需要持续向外排出大量氧气,以带走烧结过程中产生的水分,而实现上述效果的前提是降低装钵量,这不仅极大浪费了氧气,还降低了窑炉的产能

Benefits of technology

[0022](1)通过对物料进行预烧结处理,排除物料中的水分,提高物料松装密度,可极大提升装钵量,抑制物料结块,提高窑炉产能,并减少后续工序中氧气的浪费。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116404123B_ABST
    Figure CN116404123B_ABST
Patent Text Reader

Abstract

The application provides a preparation method of a low-cost high-performance high-nickel positive electrode material, comprising the following steps: s1, pre-sintering: uniformly mixing a high-nickel precursor, a lithium source and an additive, and sintering in an oxygen atmosphere to obtain a pre-sintering product; s2, high-oxygen-pressure sintering: supplementing the pre-sintering product with a lithium source, and sintering in a high-oxygen-pressure environment to obtain a high-oxygen-pressure sintering product; s3, coating sintering: uniformly mixing the high-oxygen-pressure sintering product with H3BO3 and oily PVDF after crushing and sieving, and sintering in an oxygen atmosphere to obtain the high-nickel positive electrode material. The application can improve the material loading capacity by pre-sintering water removal, can improve the kiln capacity and reduce the waste of oxygen in the subsequent process, can abandon the water washing alkali removal process, and can utilize the high-oxygen-pressure sintering technology, so that the production cost can be reduced, the utilization rate of the lithium source can be improved, the safety performance and the processing performance of the material can be improved, the residual alkali on the surface of the material can be effectively reduced, and the storage performance and the cycle performance of the material can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium battery manufacturing technology, and in particular to a method for preparing a low-cost, high-performance high-nickel cathode material. Background Technology

[0002] Lithium-ion batteries are widely used in portable electronic devices and electric vehicles due to their advantages such as small size, high energy density, long cycle life, low self-discharge rate, and no memory effect. Currently, commonly used cathode materials for lithium-ion batteries include lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, ternary materials, and high-nickel materials. Among them, high-nickel materials are considered one of the most promising cathode materials due to their high capacity.

[0003] However, since high-nickel materials are sensitive to moisture, traditional sintering kilns need to continuously discharge a large amount of oxygen to remove the moisture generated during the sintering process. The prerequisite for achieving this effect is to reduce the amount of material packed in the kiln, which not only wastes a lot of oxygen but also reduces the kiln's production capacity.

[0004] Furthermore, as the nickel content increases, the sintering conditions become increasingly demanding, making it difficult to form cathode materials with specific lithium salt ratios. This results in higher residual lithium in the products, directly leading to poorer storage performance. In materials with high nickel content, residual lithium is more likely to react with carbon dioxide and water in the air to form residual lithium carbonate and lithium hydroxide alkalis. Excessive residual alkali not only reduces the cycle performance of the material but also increases the internal resistance of the battery and makes it prone to gas expansion, reducing battery safety. Simultaneously, materials with high residual lithium exhibit poor slurry flowability during later electrode material fabrication, resulting in poor material processing performance. Additionally, materials with high nickel content, in their delithiation state, exhibit... 4+ It is very unstable, has enhanced oxidative properties, and is prone to reacting with the electrolyte, resulting in high interfacial resistance. This leads to rapid capacity decay, poor cycle performance, and increased internal resistance, which greatly limits the practical application of the material.

[0005] Currently, domestic manufacturers generally address the problem of excessive residual alkali in high-nickel materials by washing with water or coating the material surface with oxides. However, washing with water reduces the material's capacity and cycle performance. Coating the material surface with oxides, on the other hand, can hinder lithium ion delivery during the lithium ion insertion / extraction process because these coatings do not contain lithium ions. Summary of the Invention

[0006] The purpose of this invention is to provide a low-cost, high-performance method for preparing high-nickel cathode materials. Through the combined effects of pre-sintering, high-oxygen-pressure sintering, and coating sintering, the production capacity is improved and the safety, electrochemical, and processing performance of the materials are enhanced.

[0007] The technical solution adopted in this invention is: a method for preparing a low-cost, high-performance high-nickel cathode material, comprising the following steps:

[0008] s1. Pre-sintering: The high-nickel precursor, lithium source and additives are mixed and sintered in an oxygen atmosphere to obtain the pre-sintered product.

[0009] s2, High oxygen pressure sintering: Lithium source is added to the pre-sintered product, and it is sintered in a high oxygen pressure environment to obtain a high oxygen pressure sintered product;

[0010] s3. Coating and sintering: The high oxygen pressure sintering product is crushed and sieved, then mixed evenly with H3BO3 and oily PVDF, and sintered in an oxygen atmosphere to obtain the high nickel cathode material.

[0011] Furthermore, the high-nickel precursor is Ni x Co y Mn (1-x-y) (OH)2 or Ni x Co y Al (1-x-y) (OH)₂, of which 0.8 <x<0.98,0.01<y<0.2。

[0012] Furthermore, the lithium source is one or more of LiOH, LiOH·H2O and Li2CO3, and in step s1, the molar ratio of lithium in the lithium source to the high-nickel precursor is Li / Me = (0.8~1.0):1.

[0013] Furthermore, the additive is one or more of Sb2O3, Ta2O5, Nb2O3, Mo2O3, WO3, ZrO2, Al2O3, TiO2, CeO2 and La2O3, and the metal element doping amount is 0.1%mol to 5.0%mol.

[0014] Furthermore, in step s1, the pre-sintering temperature is 450℃~750℃, and the pre-sintering time is 5h~12h.

[0015] Furthermore, in step s2, the high oxygen pressure sintering temperature is 650℃~850℃, the high oxygen pressure sintering time is 8h~20h, and the oxygen partial pressure in the high oxygen pressure environment is 300~700Pa.

[0016] Furthermore, in step s2, a lithium source is added to the pre-sintered product to adjust the Li / Me ratio to (1-1.03):1.

[0017] Furthermore, in step s3, the coating sintering temperature is 180℃~700℃, and the sintering time is 3h~12h.

[0018] Furthermore, in step s3, the particle size of the high oxygen pressure sintering product after sieving is 3μm to 5μm.

[0019] Furthermore, in step s3, the coating amount of H3BO3 is 0.1wt% to 2.0wt%, and the coating amount of oily PVDF is 0.1wt% to 2.0wt%.

[0020] Furthermore, the oxygen concentration in the oxygen atmosphere and the high-oxygen-pressure environment is ≥90%.

[0021] The beneficial effects of this invention are:

[0022] (1) By pre-sintering the material, the moisture in the material is removed, the loose density of the material is increased, the amount of material can be greatly increased, the agglomeration of the material is suppressed, the kiln capacity is increased, and the waste of oxygen in subsequent processes is reduced.

[0023] (2) The water washing and alkali removal process was abandoned, and high oxygen pressure sintering technology was used instead to promote Ni 2+ To Ni 3+ The conversion avoids the traditional sintering technology's reliance on high Li / Me to promote the synthesis of high-nickel cathode materials. This not only reduces production costs, improves the utilization rate of lithium sources, and enhances the safety and processing performance of materials, but also effectively reduces residual alkali on the material surface, thereby improving the material's storage and cycle performance.

[0024] (3) The preparation method has simple procedures and low cost, which is conducive to the industrial production of the product. Attached Figure Description

[0025] Figure 1 Here are SEM images of the high-nickel cathode material prepared using the preparation method provided in the embodiments of this invention.

[0026] Figure 2 These are water transport performance test diagrams of the high-nickel cathode materials prepared in Example 1 and Comparative Example 1 of this invention. Detailed Implementation

[0027] Embodiments of the present invention are described in detail below. Examples of these embodiments are illustrated in the accompanying drawings, wherein the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain the present invention, and should not be construed as limiting the present invention.

[0028] This invention provides a method for preparing a low-cost, high-performance high-nickel cathode material, comprising the following steps:

[0029] s1. Pre-sintering: Mix the high-nickel precursor, lithium source and additive uniformly, place the mixture in an oxygen atmosphere, and sinter at a temperature of 450°C to 750°C for 5h to 12h to obtain a pre-sintered product.

[0030] In this step, the high-nickel precursor is Ni x Co y Mn (1-x-y) (OH)₂ or Ni x Co y Al (1-x-y) (OH)₂, where 0.8<x<0.98, 0.01<y<0.2; the lithium source is one or more of LiOH, LiOH·H₂O and Li₂CO₃, and the molar ratio of lithium in the lithium source to the high-nickel precursor Li / Me=(0.8~1.0):1; the additive is one or more of Sb₂O₃, Ta₂O₅, Nb₂O₃, Mo₂O₃, WO₃, ZrO₂, Al₂O₃, TiO₂, CeO₂ and La₂O₃, and the doping amount of metal elements is 0.1 mol% to 5.0 mol%.

[0031] In this step, the pre-sintering treatment of the material removes the moisture in the material, increases the loose packing density of the material, thereby increasing the loading amount into saggars, inhibiting the caking of the material, and improving the production capacity; the additive can reduce the reaction between the high-nickel cathode material and the electrolyte, improve the structural stability of the high-nickel cathode material during the charge and discharge process, and is conducive to the improvement of cycle performance.

[0032] s2. High oxygen pressure sintering: Adjust the Li / Me molar ratio of the pre-sintered product to (1~1.03):1, place it in a high oxygen pressure environment with an oxygen partial pressure of 300 to 700 Pa, and sinter at a temperature of 650°C to 850°C for 8h to 20h to obtain a high oxygen pressure sintered product.

[0033] In this step, by adjusting the inlet air flow rate of the kiln and the opening of the air exhaust vent, the pre-sintered product is sintered under high oxygen pressure conditions. A relatively high oxygen pressure is beneficial to Ni 2+ conversion to Ni 3+ , which synthesizes a high-nickel cathode material with a high stoichiometric ratio, avoids the dependence of traditional sintering technology on a high Li / Me ratio to promote the synthesis of high-nickel materials, reduces the waste of lithium source, and at the same time reduces residual lithium, improving the processability and storage performance of the material.

[0034] s3. Coating and sintering: After the high oxygen pressure sintered product is crushed and sieved, the particle size of the sieved high oxygen pressure sintered product is 3 μm to 5 μm, mix it uniformly with H₃BO₃ and oily PVDF, place the mixture in an oxygen atmosphere, and sinter at a temperature of 180°C to 700°C for 3h to 12h to obtain the high-nickel cathode material.

[0035] In this step, the coating amount of H3BO3 is 0.1wt% to 2.0wt%, and the coating amount of oily PVDF is 0.1wt% to 2.0wt%.

[0036] This step involves the reaction of H3BO3 with the residual alkali on the material surface to generate a Li2O-2B2O coating layer. This coating layer has strong ionic conductivity, which is beneficial for lithium ion transport, reduces internal resistance, reduces polarization loss, and improves the cycle performance and safety performance of the high-nickel cathode material.

[0037] On the other hand, due to the good hydrophobicity of oily PVDF, some of the oily PVDF can form a hydrophobic protective layer on the material surface, reducing the sensitivity of the high-nickel cathode material to water and improving the material's storage performance; another part of the oily PVDF decomposes and reacts with the residual alkali on the surface of the high-nickel cathode material to generate a LiF protective layer, further reducing the residual alkali content, while also improving the structural stability of the material surface and improving the product's cycle performance and storage performance.

[0038] In some embodiments, the oxygen concentration in the above-mentioned oxygen atmosphere and high oxygen pressure environment is ≥90%.

[0039] This invention has undergone multiple experiments, and some of the experimental results are listed below for reference to further describe the invention in detail. The following is a detailed description in conjunction with specific embodiments.

[0040] Example 1:

[0041] s1. Pre-sintering: Weigh Ni according to the molar ratio of lithium to high-nickel precursor Li / Me = 1:1. 0.96 Co 0.03 Al 0.01 (OH)2 and LiOH were added, along with 0.5 mol% Sb2O3 and 0.2 mol% WO3, and mixed evenly. The mixture was then placed in a furnace with an oxygen concentration of 97% and sintered at 650°C for 8 hours to obtain the pre-sintered product.

[0042] s2. High oxygen pressure sintering: LiOH is added to the pre-sintered product to adjust the Li / Me ratio to 1.01:1. The product is then placed in an atmosphere furnace with an oxygen partial pressure of 500 Pa and an oxygen concentration of 97% and sintered at 720 °C for 12 h to obtain the high oxygen pressure sintered product.

[0043] s3. Coating sintering: After crushing and sieving the high oxygen pressure sintering product, the particle size of the sieved high oxygen pressure sintering product is 3μm to 5μm. Then, 0.2wt% H3BO3 and 0.3wt% oily PVDF are added to it and mixed evenly. The mixture is placed in a furnace with an oxygen concentration of 97% and sintered at 250℃ for 6 hours to obtain high nickel cathode material.

[0044] Example 2:

[0045] The difference from Example 1 is that in step s2, LiOH is added to the pre-sintered product to adjust the Li / Me ratio to 1.02:1; in step s3, the coating amounts of H3BO3 and oily PVDF are 0.5wt% and 1.0wt%, respectively, and the coating sintering temperature is 300℃; the remaining steps and conditions are the same as in Example 1.

[0046] Example 3:

[0047] The difference from Example 1 is that the doping amounts of Sb2O3 and WO3 in step s1 are 1.0 mol% and 0.5 mol%, respectively; in step s2, LiOH is added to the pre-sintered product to adjust the Li / Me ratio to 1.02:1; the remaining steps and conditions are the same as in Example 1.

[0048] Example 4:

[0049] The difference from Example 1 is that in step s2, LiOH is added to the pre-sintered product to adjust the Li / Me ratio to 1.02:1, the high oxygen pressure sintering temperature is 710°C, and the sintering time is 18h; the remaining steps and conditions are the same as in Example 1.

[0050] SEM images of the high-nickel cathode material prepared using the preparation method provided in this embodiment of the invention are attached. Figure 1 As shown.

[0051] Comparative Example 1:

[0052] (1) Weigh Ni according to the molar ratio of lithium to high-nickel precursor Li / Me = 1.05:1. 0.96 Co 0.03 Al 0.01 (OH)2 and LiOH are mixed evenly and placed in a furnace with an oxygen concentration of 97%. The mixture is first sintered at 550°C for 5 hours and then sintered at 720°C for 12 hours to obtain the primary sintered material.

[0053] (2) The sintered material is crushed and sieved, then washed with water at 15°C for 10 minutes at a solid-liquid ratio of 1:1, and then dried in a vacuum oven at 150°C for 8 hours to obtain the washed material.

[0054] (3) The washed material was placed in an atmosphere furnace with an oxygen concentration of 97% and sintered at 700°C for 6 hours to obtain a high-nickel cathode material.

[0055] Comparative Example 2:

[0056] (1) Weigh Ni according to the molar ratio of lithium to high-nickel precursor Li / Me = 1.05:1. 0.96 Co0.03 Al 0.01 (OH)2 and LiOH are mixed evenly and placed in a furnace with an oxygen concentration of 97%. The mixture is first sintered at 550°C for 5 hours and then sintered at 720°C for 12 hours to obtain the primary sintered material.

[0057] (2) The sintered material is crushed and sieved to obtain high-nickel cathode material.

[0058] Comparative Example 3:

[0059] The difference from Comparative Example 2 is that 0.5 mol% Sb2O3 and 0.2 mol% WO3 were added as additives during mixing in step (1), while the remaining steps and conditions were the same as those in Comparative Example 2.

[0060] Comparative Example 4:

[0061] The difference from Example 1 is that the oxygen partial pressure in the atmosphere furnace in step s2 is a slightly positive pressure (1-10 Pa).

[0062] Residual alkali content detection:

[0063] The residual alkali of the high-nickel cathode materials prepared in Examples 1-4 and Comparative Examples 1-4 were tested using the following methods.

[0064] (1) Weigh 20.0±0.1g of sample into a dry and clean conical flask of 150~250mL, record the mass of the sample (m1), add 100mL of distilled water and record the mass of the added water (m2), add a magnetic stir bar to the conical flask, cover with plastic wrap, and stir for 5min.

[0065] (2) After stirring, let stand for 1-2 minutes, filter the supernatant, and take about 30 mL;

[0066] (3) Transfer 20 mL of filtrate into a 150-250 mL Erlenmeyer flask and record the mass of the filtrate (m3). Add 1 drop of phenolphthalein as an indicator to the Erlenmeyer flask. The solution will turn red. Titrate with 0.1 mol / L hydrochloric acid until the solution is colorless and record the amount of hydrochloric acid used (V1). Add 1 drop of methyl orange indicator. The solution will turn yellow. Continue to titrate with 0.1 mol / L hydrochloric acid until the solution turns orange-yellow and record the amount of hydrochloric acid used (V2).

[0067] (4) Formula for calculating Li2CO3 content:

[0068] Li2CO3=C(HCl)×2(V2-V1)×N1×m2 / m1 / m3 / 2 / 1000×100%.

[0069] Formula for calculating LiOH content:

[0070] LiOH=C(HCl)×(2V1-V2)×N2×m2 / m1 / m3 / 1000×100%.

[0071] Li in residual alkali + Formula for calculating content:

[0072] Li + =Li2CO3×N3×2 / N1+LiOH×N3 / N2.

[0073] in:

[0074] N1 is the molar mass of Li2CO3, 73.89 g / mol;

[0075] N2 is the molar mass of LiOH, 23.95 g / mol;

[0076] N3 is Li + Its molar mass is 6.941 g / mol.

[0077] Table 1 Results of residual alkali content detection

[0078] Example 1 0.322% 0.334% 0.156% Example 2 0.393% 0.356% 0.181% Example 3 0.382% 0.335% 0.174% Example 4 0.357% 0.352% 0.170% Comparative Example 1 0.349% 0.332% 0.164% Comparative Example 2 0.621% 0.543% 0.282% Comparative Example 3 0.594% 0.503% 0.267% Comparative Example 4 0.386% 0.374% 0.182%

[0079] Comparing the above data, Comparative Example 1 used traditional water washing technology to remove residual alkali, resulting in a lower residual alkali content. Comparative Examples 2 and 3 did not undergo a residual alkali removal process, resulting in higher residual alkali content. Analyzing the test results of Examples 1-4, by adjusting the amount of additive in step s1, the amount of lithium source added in step s2, the amount of H3BO3 and oily PVDF in step s3, and the sintering temperature and time, Example 1 obtained a high-nickel cathode material with a lower residual alkali content than Comparative Example 1, indicating that the embodiments of the present invention can effectively reduce the residual alkali content on the surface of high-nickel cathode materials. In addition, Comparative Example 4, which used micro-positive pressure sintering, had more unreacted Li, causing an increase in the residual alkali content of the high-nickel cathode material in Comparative Example 4. However, Example 1 promoted Ni reduction through high oxygen pressure sintering. 2+ To Ni 3+ The conversion avoids the traditional sintering technology's reliance on high Li / Me to promote the synthesis of high-nickel cathode materials, improves the utilization rate of lithium sources, and thus reduces the residual alkali content.

[0080] Electrochemical performance testing:

[0081] The discharge capacity and cycle performance of the high-nickel cathode materials prepared in Examples 1-4 and Comparative Examples 1-4 were tested using the following methods.

[0082] Under conditions of humidity ≤10%, using Super-P as a conductive agent and PVDF solution (6wt%, solvent: NMP) as a binder, 5.400g±0.010g of high-nickel cathode material, 0.3000g±0.0010g of Super-P, and 5.000g±0.020g of PVDF solution were added, and an appropriate amount of N-methyl-2-pyrrolidone was added and stirred for 2–4 hours to prepare a paste-like cathode slurry. This slurry was uniformly coated onto aluminum foil and dried in an oven at 120℃±3℃. The dried electrode sheet was then rolled to the required thickness, and test electrodes of appropriate size were cut. After drying, the electrodes were sliced, assembled into batteries, and their discharge capacity and cycle performance were tested.

[0083] The initial discharge capacity was tested at 0.2C and 1C, respectively. The discharge capacity test conditions were: room temperature 25℃ and voltage range of 3.0~4.3V. The cycle performance test conditions were: voltage range of 3.0~4.3V, 60 cycles at 1C at 25℃, and the capacity retention rate after 60 cycles was calculated.

[0084] Table 2 Discharge capacity and cycle performance test data

[0085]

[0086] Comparing the above data, Examples 1-4 all showed high discharge specific capacity and cycle life. Comparative Example 1 used traditional water washing technology to remove residual alkali. Although the residual alkali content was lower than that of Examples 2-4, the negative impact was a reduction in the capacity and cycle life of the material. Comparative Examples 2-3 did not undergo a residual alkali removal process, so their capacity and cycle life were improved compared to Comparative Example 1, but they were still weaker than the performance of the high-nickel cathode materials of Examples 1-4. Comparative Example 4, which used micro-positive pressure sintering, had more unreacted Li, resulting in low capacity and poor cycle life of the material.

[0087] Hydrophobicity test:

[0088] The high-nickel cathode materials prepared in Example 1 and Comparative Example 1 were laid flat, and a drop of water was dropped in the center of each material. After standing for 30 seconds, the water penetration state in the material was observed.

[0089] The test results are attached. Figure 2 As shown, after water was dripped, the water droplets on the surface of Comparative Example 1 quickly penetrated into the material, while the water droplets on the surface of Example 1 remained on the material surface. This indicates that the material treated by the coating and sintering process in the embodiments of the present invention has good hydrophobicity, which can reduce the material's sensitivity to water and is beneficial to improving the material's storage performance.

[0090] In summary, the preparation method provided by the embodiments of the present invention is simple and reliable, suitable for industrial production. By pre-sintering to remove water and increase the material loading, the kiln capacity can be increased and the waste of oxygen in subsequent processes can be reduced. By abandoning the water washing and alkali removal process and using high oxygen pressure sintering technology, the traditional sintering technology relies on high Li / Me to promote the synthesis of high nickel cathode materials. This not only reduces production costs, improves the utilization rate of lithium sources, and improves the safety and processing performance of materials, but also effectively reduces residual alkali on the material surface and improves the storage and cycle performance of materials.

[0091] It should be understood that the specific embodiments described above are merely illustrative or explanatory of the principles of the invention and do not constitute a limitation thereof. Therefore, any modifications, equivalent substitutions, improvements, etc., made without departing from the spirit and scope of the invention should be included within the protection scope of the invention. Furthermore, the appended claims are intended to cover all variations and modifications falling within the scope and boundaries of the claims, or equivalent forms of such scope and boundaries.

Claims

1. A method for preparing a low-cost, high-performance high-nickel cathode material, characterized in that, Including the following steps: s1. Pre-sintering: The high-nickel precursor, lithium source, and additives are mixed and sintered in an oxygen atmosphere to obtain a pre-sintered product; the pre-sintering temperature is 450℃~750℃, and the pre-sintering time is 5h~12h; the lithium source is one or more of LiOH, LiOH·H2O, and Li2CO3, and the molar ratio of lithium in the lithium source to the high-nickel precursor is Li / Me=(0.8~1.0):1; s2. High oxygen pressure sintering: Lithium source is added to the pre-sintered product to adjust the Li / Me ratio to (1~1.03):1, and the product is sintered in a high oxygen pressure environment to obtain a high oxygen pressure sintered product; the high oxygen pressure sintering temperature is 650℃~850℃, and the high oxygen pressure sintering time is 8h~20h. s3. Coating sintering: The high oxygen pressure sintering product is crushed and sieved, then mixed evenly with H3BO3 and oily PVDF, and sintered in an oxygen atmosphere to obtain the high nickel cathode material; the coating sintering temperature is 180℃~700℃, and the sintering time is 3h~12h. The high-nickel precursor is Ni x Co y Mn (1-x-y) (OH)2 or Ni x Co y Al (1-x-y) (OH)₂, of which 0.8 <x<0.98,0.01<y<0.2; The additive is one or more of Sb2O3, Ta2O5, Nb2O3, Mo2O3, WO3, ZrO2, Al2O3, TiO2, CeO2 and La2O3, and the metal element doping amount is 0.1%mol to 5.0%mol; In a high-pressure oxygen environment, the partial pressure of oxygen is 300~700 Pa, and the oxygen concentration is ≥90%. The coating amount of H3BO3 is 0.1wt%~2.0wt%, and the coating amount of oily PVDF is 0.1wt%~2.0wt%.

2. The method for preparing a low-cost, high-performance high-nickel cathode material according to claim 1, characterized in that, In step s3, the particle size of the high oxygen pressure sintering product after sieving is 3μm~5μm.

Citation Information

Patent Citations

  • Nickel-cobalt-manganese ternary positive electrode spherical material and preparation method thereof

    CN109873145A

  • Organic adhesive film loaded active carbon and boron co-coated positive electrode material and preparation method

    CN110444762A

  • Composite coating agent for positive electrode material, high-nickel single-crystal positive electrode material and battery

    CN115036493A

  • Low-cobalt ternary single-crystal positive electrode material, preparation method thereof and lithium ion battery

    CN115477333A